THE ROLE OF LANGUAGE IN SHAPING GENDER AND SEXUALITY IN EUROPE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Language is a fundamental cultural tool that influences and reflects societal norms. In Europe, where linguistic diversity meets evolving social attitudes, language plays a critical role in shaping perceptions of gender and sexuality. This article explores how grammatical structures, societal norms, and linguistic reforms contribute to shaping and challenging traditional views on gender and sexuality across the continent